Leveraging Renewable Energy for Geopolitical Influence: Indonesia's Role in the Global Energy Transition - Syarifah, Claudia (JURNAL HUBUNGAN LUAR NEGERI, 2025)
Indonesia possesses vast renewable energy resources, including geothermal, solar, hydropower, and biomass, positioning the country as a crucial player in the global shift from fossil fuels to sustainable energy sources. This paper examines the barriers that hinder Indonesia’s ability to fully tap into its renewable energy potential, such as policy inefficiencies, insufficient infrastructure, and limited financial support. By analyzing Indonesia's energy diplomacy and its participation in regional initiatives like the ASEAN Power Grid, the study explores how the country can enhance its geopolitical influence through leadership in renewable energy. The findings suggest that overcoming these challenges not only allows Indonesia to address its own energy needs but also strengthens its role in shaping global energy policies and contributing to climate change solutions. Renewable energy, geopolitical influence, Indonesia, ASEAN Power Grid, energy diplomacy, energy transition